If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 3a + -7 + -6 = 8 + -3a Reorder the terms: -15 + -7 + -6 + 3a = 8 + -3a Combine like terms: -15 + -7 = -22 -22 + -6 + 3a = 8 + -3a Combine like terms: -22 + -6 = -28 -28 + 3a = 8 + -3a Solving -28 + 3a = 8 + -3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3a' to each side of the equation. -28 + 3a + 3a = 8 + -3a + 3a Combine like terms: 3a + 3a = 6a -28 + 6a = 8 + -3a + 3a Combine like terms: -3a + 3a = 0 -28 + 6a = 8 + 0 -28 + 6a = 8 Add '28' to each side of the equation. -28 + 28 + 6a = 8 + 28 Combine like terms: -28 + 28 = 0 0 + 6a = 8 + 28 6a = 8 + 28 Combine like terms: 8 + 28 = 36 6a = 36 Divide each side by '6'. a = 6 Simplifying a = 6
| 18-3x=5x-22 | | 1.2x-0.8=13/5x-18/5 | | 3x-15=4x+18 | | x^2-2.55x+4.5=0 | | 16x^3-16x^2-3=0 | | 6v-10=104 | | 78d+4=160 | | 4(y-9)=3(2-8) | | 3x+14=7x+19 | | -26+8n=-8(-8-4n)-6n | | 20y+7=15 | | 8x-64x^(-1/2)=0 | | 78=-6r | | g-2=(4g-2)/4 | | 9k^2-6k-9=0 | | 5e+7=17 | | 53-4x=29-3x | | 35-3x=14-10x | | 3x-24=4x-8 | | 1-3x(1)-(-3)-2(x-3)=3x-(-4) | | 2x+7=6x+19 | | (8x-64x^(-1/2)) | | -(8v-7)=25-5v | | -7f=56 | | (7x+1)(8x-6)= | | x+7=3x+9.5 | | (x^(2/3)y^(-(5/4)))^6 | | 1.4/7.7 | | lg(x^2-x-6)-lg(x-3)=0 | | 25x^2+35x=0 | | 5=-7+a | | 40=-8(x+2) |